Teaching English Language through “Spelling Bee” Games in Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discusses the limitations of using subject scores as definitive evidence of students' proficiency in learning a new language. It highlights the fact that students who received good or satisfactory grades had a higher number of words spelled correctly in comparison with students who had excellent grades, indicating a correlation between spelling skills and academic performance. However, this correlation does not necessarily imply language proficiency in general.